Sonorejo Culture Village Documentary Menggunakan Aplikasi Sony Vegas 13.0 - Devi Rizki Zahrahwani (Politeknosains, 2018)
This research aims to spread the means as information about artisans or arts businessmen in Sonorejo area. Previously some people who know about the efforts that exist in the area of sonorejo.information packed in a video is expected to provide information to the public and can be understood, understood by the audience and can be used as a document in the village of Sonorejo. The main software used is the Sony Vegas 13.0. The entire video is a duration of 5.4 minutes consisting of 20 scenes. The products displayed include shadow puppets, drums and calligraphy paintings. The main source is the head of Sono rejo urban village, namely Mr. Widie Hastono, SE., MM. Regardless of the type and model of public service ads, basically public service advertisements should be able to carry external functions with media that provide information clearly, attractively and easily understood by the public in outline.